Place Process in Space with Territorial Ambivalence Case Study: Suronatan, Yogyakarta - Fitria, Tika Ainunnisa; Pujiyanti, Indah (Universitas Muhammadiyah Surakarta, 2026)
The existence of the Village is closely related to the morphology, history, and philosophy of the city of Yogyakarta and is related to the socio-spatial life and its people. Kampung Suronatan experiences intersections of activities that have an impact on the formation of spontaneous spaces along its transitional space. Physical changes in the transitional space and the phenomenon of utilization and territorial claims. This research question refers to how the place process occurs in Kampung Suronatan, as a space with territorial ambivalence. This research was conducted qualitatively, focusing on spatiality and its behavior as a space former. Data were obtained through snapshot observations and short questions which were then analyzed using a behavioral approach. ArcGIS was used to map the location of spontaneous spaces formed in the transitional space. Place process in the transitional space in Suronatan is influenced by spatial tolerance and spatial conceptions influenced by local norms related to spatial territoriality. Place process is defined as a process of spatialization that is spontaneous and temporal. Enriching the theory of place process that has not been linked to territoriality.